Sebuah Analisis Tentang Sebab-Sebab Kejadian Kecelakaan KM. Putri Ayu di Perairan Pulau Ambon-Maluku - Hanok Mandaku (Industrial Engineering Study Program, Pattimura University, 2012)
Accident of KM. Putri Ayu at June 17, 2012 in sea of Asilulu, Ambon Island-Maluku, leaving of problem: what its cause factor?; how its contribution?; and what its step to prevent similar accident in future? This research have the character of analytic descriptive, as a mean to explain about factors cause of accident of sea transportation with analyse at occurence of KM. Putri Ayu, and also invite stakeholders to be more comprehend in importance security and safety of sea transportation and generated risk effect of anticipatory negligence of factors, also repair recommendations to stakeholder in others sea transportation. Output of analysis indicated there are 3 (three) factors have contribution in accident KM Putri Ayu, that is (1) negligence of regulator; (2) technical condition of ship; and (3) weather is extreme. For that, utilize to guarantee its form of safety and reliable ship security system in Moluccas, te future : (1) Improving cooperation in between crew of ship, owner and regulator; ( 2) Improving maintenance system of ship; and ( 3) Existence of comprehensive analysis to condition of every sea transport.